Legal analysis of the procedure for the formation of the law of the republic of Indonesia - Mustamin Mustamin; Muhammad Azhar Nur (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Laws are a type of legislation whose formation process takes a long time with lengthy procedures. This study aims to examine the mechanism for the formation of laws and regulations in Indonesia. This research uses a descriptive normative approach, namely by explaining or legislation, legal theories, the teachings of the science of law as well as the opinions of leading scholars. The result of this study show that the process of forming laws and regulations in Indonesia is still facing various obstacles so that to finalize a product of the legislative body's law together with the government requires a relatively long time. The draft bill queues according to the priority scale in the National Legislation Program. The normal procedure for forming laws in Indonesia starts from the stages of planning, drafting, discussing, ratifying or enacting until promulgation is a process that takes quite a long time to go through discussions and debates in the legislature to find common ground and agreement. It is not always possible to predict when the process will end at the enactment stage. Meanwhile, the community's need for legal certainty is a more important matter to be fulfilled immediately.